2017
DOI: 10.1177/0735633117707312
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness Roles of Variables in the Novice Programmers Learning

Abstract: This research applies the roles of variables to the novice programmers in the C language programming. The results are evaluated using the Structure of Observed Learning Outcomes (SOLO) taxonomy. The participants were divided into an experimental group and a control group. The students from the control group learned programming in the traditional case-based teaching method. The students in the experimental group learned programming by applying the role-based approach to the case-based teaching method. For the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 40 publications
(74 reference statements)
0
17
0
Order By: Relevance
“…That is to say, if they are well understanding the variables, they might master learning in sequencing, brunching, and repeating algorithms concerning computer programming languages. When students have incomplete and incorrect understandings of variables, they will have difficulties writing programs (Shi et al, 2018). The research reported that undergraduate and K-12 novices mostly did incomplete and incorrect understandings of the purpose and ways to use the variables (Kwon, 2017).…”
Section: Variable Misconceptions In Computer Programmingmentioning
confidence: 99%
See 1 more Smart Citation
“…That is to say, if they are well understanding the variables, they might master learning in sequencing, brunching, and repeating algorithms concerning computer programming languages. When students have incomplete and incorrect understandings of variables, they will have difficulties writing programs (Shi et al, 2018). The research reported that undergraduate and K-12 novices mostly did incomplete and incorrect understandings of the purpose and ways to use the variables (Kwon, 2017).…”
Section: Variable Misconceptions In Computer Programmingmentioning
confidence: 99%
“…Computer programming learning is fundamental for K-12 students to deepen their understanding of computer science skills (Fessakis et al, 2013). Furthermore, Shi et al (2018) argued that variables could be fundamental to effective writing computer programs.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that nonlinear reading skills increased with expertize levels, and that instructors and students could monitor their own progress using eye-tracking tools. In a study of Shi et al [46], they evaluated the effectiveness roles of variables in novice programmers learning C programming, and found a strong positive correlation between their reading and writing, which suggested that students need to learn how to read programs before learning how to write them.…”
Section: Instructional Techniques and Teaching Strategiesmentioning
confidence: 99%
“…These results reveal that students did not understand the purpose and ways to use of variables. Regarding the issue, Shi, Cui, Zhang, and Sun (2017) suggest that novice programmers encounter difficulty understanding a code and writing a program when they do not figure out the functions of variables.…”
Section: Misuse Of Variablesmentioning
confidence: 99%